The Impact of augmented reality media integrated with ethnomathematics on students' numeracy literacy skills - Pasaribu, Rotua Saulina; Husna, Asmaul; Hanggara, Yudhi (CAHAYA PENDIDIKAN, 2024)
The problem of students' numeracy literacy is a major concern in mathematics education. This study aims to explore the impact of the application of Augmented Reality (AR) media integrated with Limas Potong traditional house on students' numeracy literacy skills. The research method used was pre-experimental with one class group as the research subject. A total of 22 students of class VIII F MTs USB Filial MTsN 1 Batam became research subjects. The instrument used was an essay-shaped test to measure numeracy literacy which was adjusted to the material taught. Data analysis was carried out by parametric one tailed sample t-test after ensuring normal data distribution. The results showed that the use of AR media integrated with the Limas Potong traditional house had a positive impact on improving students' numeracy literacy skills. The integration of AR media allows students to experience firsthand the structure and characteristics of the traditional house, thus making math learning more interesting. This research contributes to the development of innovative and interesting mathematics learning methods through the use of Augmented Reality media in the context of Indonesian traditional houses.